Factors Affecting Taxpayer Compliance - Mariana, Citra; Andari, Diah; Andriana, Nadila (Jurnal Edukasi (Ekonomi, Pendidikan dan Akuntansi), 2024)
The aim of this study is to investigate how taxpayer awareness and tax sanctions affect individual taxpayer compliance at the Bandung Cicadas Pratama Tax Service Office. The study population comprises 102.520 individual taxpayers registered at KPP Pratama Bandung Cicadas in 2022. The sample size for this research is 100 individual taxpayers registered at the Bandung Cicadas Pratama Tax Service Office. The data analysis method in this research uses multiple regression analysis. The findings suggest that taxpayer awareness and tax sanctions have a significant impact on the compliance of individual taxpayers registered at the Bandung Cicadas Pratama Tax Service Office. However, tax socialization does not seem to influence the compliance of individual taxpayers in this office.